ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, OPERATIONAL EFFICIENCY, NON PERFORMING LOAN, DAN LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSET PADA BANK BUMN DI INDONESIA - Ronny Chandra (Program Magister Akuntansi Unsyiah, 2013)
This research aimed to analyse the influence of Capital Adequacy Ratio (CAR), Operational Efficiency (BOPO), Non Performing Loan (NPL), and Loan to Deposit Ratio (LDR) on Return On Asset (ROA) of State-Owned Enterprise Banks in Indonesia. The data was obtained from the Published Financial Report publised by Indonesian Bank in the period of 2008-2012 with 80 datas as the total of population in this research. Analysis technique used was a double regression with the smallest square equation and the hypothesis test used F-statistic to test the truth of collective influence and also t-statistic which was used to test the partial coefficient of regression with the significance level of 5%.Keywords : CAR, NPL, BOPO, LDR and ROA.